Bahasa Diplomasi Nabi Muhammad SAW - Ubaidillah ubaidillah (Alfaz (Arabic Literatures for Academic Zealots), 2018)
This article explains how the language of Prophet Muhammad’s diplomacy in his letters sent to kings. Holmes’ context analysis theory (1992) is used in this research that looks at four social factors namely: participant, setting, topic, and function. Translational method used to analyze data and to connect social factor with diplomacy language that used, writer use method of extralingual padan. The style of diplomacy is seen from its factors (1) Participant: if the letter is addressed to a non-Arab king, the reverence greeting is clearly mentioned, whereas to the ruler in the Arabian Peninsula, only the mention of nasab (lineage). (2) Setting: for letters to non-Arabic kings, not using the association language, while to the Arab king, using it. (3) Topics: To the kings, who have not embraced Islam, about the call to embrace Islam, while for the Moslem king about the regulation of Islamic norms. (4) Function: to utilize the time of ceasefire between the Muslims and the mushrik of Mecca and to spread Islam universally. In general it can be concluded that the diplomatic language of the Prophet Muhammad is very concerned about the culture of the opponent said and still use the principles of effective and efficient language used.